MYSTICAL KASHMIR: A PARADISE FOR TRAVELERS AND EXPLORERS - Shabir Ahmad Lone; Rawnaq Ara Parvin (CV. Radja Publika, 2025)
The Kashmir Valley, also called the Vale of Kashmir, is an intermontane valley in the northern region of Jammu and Kashmir, a union territory governed by India. It is a key part of the larger Kashmir region, which has been subject to territorial disputes involving India, Pakistan since 1947, and China since 1962. Enclosed by the Himalayas, with the Pir Panjal Range to the southwest and the Greater Himalayas to the northeast, the valley spans approximately 135 kilometers in length and 32 kilometers in width. The Jhelum River traverses the region, which forms a major part of the Kashmir Division. Recognized as